Transformations in the ways of being a child among the Kaiowa in Te’ýikue: everyday life and schooling - Cariaga, Diógenes (2015)
This article addresses the transformations in which childhood is experienced among the Kaiowa of te’ýikue, both in everyday life and at school. the data used for this article comes from ethnographic field research and emphasizes historical information as well as native perceptions and interpretations. The Kaiowa have experienced an intensification of their relationship with other brazilians (brancos) that has brought social and cultural transformations. Due to this process, the Kaiowa have developed specific strategies in indigenous schools related to the everyday life of their families as well as the education of their children. the article discusses different key issues such as childhood, children education and cultural transformations in dialogue with native categories.